Clinical outcomes of colorectal neoplasm with positive resection margin after endoscopic submucosal dissection - Hyung-Hoon Oh; Je-Seong Kim; Jae-Woong Lim; Chae-June Lim; Young-Eun Seo; Ga-Ram You; Chan-Muk Im; Ki-Hyun Kim; Dong-Hyun Kim; Hyun-Soo Kim; Young-Eun Joo (Scientific Reports, 2024)
Abstract A positive resection margin after colorectal endoscopic submucosal dissection (ESD) is associated with an increased risk of recurrence. We aimed to identify the clinical significance of positive resection margins in colorectal neoplasms after ESD. We reviewed 632 patients who had en bloc colorectal ESD at two hospitals between 2015 and 2020. The recurrence rates and presence of residual tumor after surgery were evaluated. The rate of additional surgery after ESD and recurrence rate were significantly higher in patients with incomplete resection (n = 75) compared to patients with complete resection (n = 557). When focusing solely on non-invasive lesions, no significant differences in recurrence rates were observed between the groups with complete and incomplete resection (0.2% vs. 1.9%, p = 0.057). Among 84 patients with submucosal invasive carcinoma, 39 patients underwent additional surgery due to non-curative resection. Positive vertical margin and lymphovascular invasion were associated with residual tumor. Lymphovascular invasion was associated with lymph node metastasis. However, no residual tumor nor lymph node metastases were found in patients with only one unfavorable histological factor. In conclusion, a positive resection margin in non-invasive colorectal lesions, did not significantly impact the recurrence rate. Also, in T1 colorectal cancer with a positive vertical resection margin, salvage surgery can be considered in selected patients with additional risk factors.